2010
DOI: 10.15208/beh.2010.12
|View full text |Cite
|
Sign up to set email alerts
|

Interconnected firms’ relationships as a source of a competitive advantage

Abstract: The mainstream economy poses the opinion that a competitive advantage lies in resources, and, consequently-in competences as well-being a share of a single company and remaining under its sole control. Recently, some researchers (e.g. Castaldo, 2007; Lavie, 2006) have revised that approach and tend to emphasise the role of other sources of competitive advantage in business strategy, which embrace new, intangible assets. Such assets are being born and developed only within the inter-firm relationships built in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(19 reference statements)
0
5
0
1
Order By: Relevance
“…In fact, literature revealed that the main challenges for technopreneurs are to acquire business assets, build market chains and set up an established position in the market (Kamal, Zawawi & Abdullah, 2016). Besides, Rudawska (2010) asserts that market synergy is considered as the competitive advantage and act as the benchmark for customer satisfaction. Kamal et al (2016) also noted that when firms employ MRS and collaborate with the necessary parties; then, such cooperation reinforces the market power and softens the market competition.…”
Section: Eo and Start-up Successmentioning
confidence: 99%
“…In fact, literature revealed that the main challenges for technopreneurs are to acquire business assets, build market chains and set up an established position in the market (Kamal, Zawawi & Abdullah, 2016). Besides, Rudawska (2010) asserts that market synergy is considered as the competitive advantage and act as the benchmark for customer satisfaction. Kamal et al (2016) also noted that when firms employ MRS and collaborate with the necessary parties; then, such cooperation reinforces the market power and softens the market competition.…”
Section: Eo and Start-up Successmentioning
confidence: 99%
“…The assumption of resource heterogeneity in business relationships led to the transfer of the resource-based assumptions to relational and network studies (Gold et al, 2010;Rašković and Makovec, 2013;Rudawska, 2010;Vargas and Mantilla, 2014). They revealed that competitive advantage lies in resources and intangible assets which are born and developed within the inter-firm relationships built in a network environment.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Ma ono wobec nich komplementarny charakter, a dzięki skupianiu się na zróżnicowanych aspektach relacji wzbogaca stan wiedzy na temat współpracy między przedsiębiorstwami. Wypracowane koncepcje oraz modele, w których autorzy skupiają się na relacjach i rencie relacyjnej, poszerzają możliwości zrozumienia osiągania źródeł przewagi konkurencyjnej oraz przyczyn i zasadności współpracy pomiędzy przedsiębiorstwami (Rudawska, 2010). Jak podkreśla Światowiec-Szczepańska (2012), dokonując przeglądu teorii uzasadniających współpracę przedsiębiorstw, nie istnieje jedna dominująca metateoria dotycząca współdziałania organizacji i potrafiąca wyjaśnić kompleksowo to zjawisko.…”
Section: Rysunek 2 Systemowe Podejście Do Relacji Biznesowejunclassified